LENGTH-WEIGHT STUDIES OF EPINEPHELUS CHLOROSTIGMA E. EOLATUS FROM GULF - Alkahem, Hmoud Fares; Ahmad, Zubair; Al-Dhahi, Amir Ahmad Abdur-Rahman (Journal of Indian Fisheries Association, 2015)
Regression coefficient value (b) of the length-weight relation of Epinephelus chlorostigma was registered as 2.6383, which is significantly (p<0.01) less than the hypothetical value (3). This coefficient of E. areolatus was registered as 2.9500, a value close to 3. The correlation coefficients (r) were registered as 0.9725 and 0.9837 for E. chlorostigma and E. areolatus, respectively, which show a good relationship between the two parameters. Keywords: Length-weight, Epinephelus chlorostigma, E. areolatus, Arabian Gul